(untitled) (LACCEI, 2024)
This research paper posits the use of graph theoretical models to support the data visualization required for monitoring and measuring cyber-security investments for digital firms provided with sufficient capabilities assumed to manage the cost of such investments. We present as vertices and edges within a graph that the total cost path function between vertices/nodes of a graph will be unique given that the total cost path value is dependent on the goal cost (i.e. the cost to enable the working environment) and the heuristic cost (i.e. the cost of an attack on the same working environment). This working environment are all represented as graph path cost and applies the principle of the travelling salesman problem within graph theory. Graph modeling supports the fact that we can use the nodes as points to track/determine the behavior of an investment as a function of time (t).We develop a conceptual prototype of our graph model and provide an evaluation of same based on the fundamentals from computational graph theory. This work represents the first of its kind in our region, where we use the graphs to support data visualization for the Chief Executive officers within a digital firm that need to appropriately understand his/her cyber-security investment spend